Continuous biosorption assessment for the removal of hexavalent chromium from aqueous solutions using Strychnos nux vomica fruit shell. (September 2018) - Nakkeeran, E.; Patra, Chandi; Shahnaz, Tasrin; Rangabhashiyam, S.; Selvaraju, N.
Abstract: Column biosorption studies were performed to check the potential of Strychnos nux vomica tree fruit shell (STFS) towards Cr(VI) elimination from simulated aqueous solution. Effect of various parameters like height of bed (3, 5, 7 cm), flow rate inside the column (5, 10, 15 mL/min) and initial concentration of Cr(VI) in aqueous solution (50, 100, 150 mg/L) for removal of Cr(VI) were studied. The results revealed that Cr(VI) adsorption capacity (mg/g) marked up with the rise in bed height; decreased with elevation in flow rate and initial concentrations of Cr(VI). Biosorption column models viz. Adams-Bohart Thomas, Yoon-Nelson and Bed Depth Service Time (BDST) were evaluated with the equilibrium data. Comparatively, Thomas and BDST model presented better agreement with the equilibrium data. The current investigation verified STFS, a novel lignocellulosic biosorbent (STFS) which resulted in quite reasonable biosorption capacities could be used significantly for Cr(VI) removal from wastewater. Highlights: Novel renewable biosorbent for the removal of hexavalent chromium was presented. Inlet flow rate, bed height, influent Cr(VI) concentration parameters were analyzed. The experimental data better fitted the Thomas model. Breakthrough curves of hexavalent chromium biosorption were investigated.